Microbiological profile of isolated specimens in patients admitted to a university hospital from Fortaleza, Brazil - Thalita M. FREIRE; Elana F. CHAVES; José M. ALCÂNTARA-NETO; Paulo P. SOUSA; Jorge N. RODRIGUES; Henry C. REIS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objective: To assess the microbiological profile of culture results of patients admitted in a public university hospital from Fortaleza, Brazil. Methods: This is a descriptive and prospective study with patients being followed up in an antimicrobial stewardship program and in use of reserve or strategic antimicrobial agents, which had cultures requested between May and November 2017. Data was obtained from the patient's records, registered and analyzed using Excel spreadsheets and Graph Pad Prism statistical software. Results: Male patients (60.2%), non-elderly (63.6%), with hospital discharge clinical outcome (84.7%) and kidney transplant specialty (35.6%) prevailed. We analyzed the result of 490 cultures, with a higher frequency of urine cultures (35.3%) and blood cultures (34.7%) than others cultures. The specialty with most requests was kidney and liver transplant. 19.8% of the cultures were positive, predominantly gram-negative bacilli (72.2%), especially in the urine cultures of transplant patients. Microbiological analysis showed that Klebsiella pneumoniae (49.1%) and Escherichia coli (39.6%) were the bacteria most frequently found. Regarding the microbial resistance profile, we identified carbapenemase producing bacteria (16.7%), Extended spectrum beta-lactamases (ESBL; 33.3%) within the group of gramnegative bacilli and Vancomycin-resistence enterococcus (VRE; 13.5%) within the group of gram-positive cocci. Conclusions: The study enabled the knowledge of the profile of microorganisms isolated in the wards under study, which is of fundamental importance for local epidemiological studies and for the control of microbial resistance.